Leaf epidermal micromorphology and its implications in systematics of certain taxa of the fern family Pteridaceae from Northern Pakistan. Issue 3 (23rd December 2018) - Shah, Syed Nasar; Celik, Ali; Ahmad, Mushtaq; Ullah, Fazal; Zaman, Wajid; Zafar, Muhammad; Malik, Khafsa; Rashid, Neelam; Iqbal, Majid; Sohail, Aamir; Bahadur, Saraj
Abstract : The present study is insights into foliar epidermal anatomy for characterizing clades, and their utility in taxonomic segregation of certain species of Pteridaceae from Northern Pakistan. The leaf epidermal anatomy of 10 species of Pteridaceae representing four genera were examined using light and scanning electron microscope. A micromorphological matrix was constructed for eight qualitative and 12 quantitative characters. unweighted pair group method with arithmetic means and principal components analysis statistical analysis were performed to test the validity of foliar epidermal anatomical features as method of separating species and genera, and phylogenetic clusters among species are constructed using qualitative and quantitative traits. The qualitative characters described here are shape of epidermal cells, stomata, guard cell and subsidiary cells, anticlinal wall pattern, and trichomes types which is helpful in defining groups within Pteridaceae. In addition, the size of stomata, guard cells, subsidiary cells, stomatal pore epidermal cells, and trichomes are quantitatively analyzed. All species have hypostomatic leaves. Two types of stomata were observed in studied species, anomocytic and polocytic. Anomocytic stomata were observed in three genera namely: Adiantum, Onychium, and Chielanthes whereas Pteris can be discriminated from other genera by its polocytic stomata. On the basis of multivariate analysis present study does provides sufficient information on the taxonomic importance of foliar anatomy which validate its efficacy in species and genera discrimination. From result obtained here it is further possible to use leaf micromorphologic data in ferns phylogeny and providing basis for future taxonomic delimitation in other taxa. Abstract : Taxonomic significance of leaf micromorphology in Pteridaceae is described. Variation in quantitative and qualitative characters were found useful in the identification and discrimination of Pteridaceae species. Principal components analysis and unweighted pair group method with arithmetic means cluster analysis is performed in Pteridaceae which is based on qualitative and quantitative traits.